Biobrane versus topical agents in the treatment of adult scald burns - Krezdorn, Nicco; Tapking, Christian (Burns, 2017)
Background: Limited data is available for treatment of scald lesions in adults. The use of the biosynthetic matrix Biobrane® has been suggested as treatment option with more benefits over topical dressings. Application of Biobrane® in scalds in our center led to a perceived increase of infection, secondary deepening, surgery and length of stay. We therefore assessed the effect of different treatment options in adult scalds in our center. Methods: We performed a retrospective cohort study of adult patients that have been admitted with scalds in our center between 2011 and 2014. We assessed two groups, group 1 with Biobrane® as initial treatment and group 2 with topical treatment using polyhexanid hydrogel and fatty gauze. Primary outcome variables were rate of secondary deepening, surgery, infection (defined as positive microbiological swabs and antibiotic treatment) and length of stay. Total body surface area (TBSA) as well as diabetes mellitus (DM), hypertension, smoking and alcohol consumption as potential confounders were included. Results: A total of 52 patients were included in this study. 36 patients received treatment with Biobrane® and 16 with ointment and fatty gauze. No significant differences were found for age and TBSA whereas gender ratio was different (25/11 male/female in group 1 vs 4/12 in group 2, p=0.003). Rate of secondary deepening, surgery, infection as well as days of hospital stay (DOHS) were comparable. Logistic and multilinear regression showed TBSA to be a predictive factor for infection (p=0.041), and TBSA and age for length of stay (age p=0.036; TBSA p=0.042) in group 1. Conclusion: The use of Biobrane® in adult scald lesions is safe and non-inferior to topical treatment options. In elder patients and larger TBSA Biobrane® may increase the risk of infection or a prolonged stay in hospital. LEVEL OF EVIDENCE: Level 3 - retrospective cohort study.